Estudio de prácticas judiciales inclusivas desde el modelo social y su impacto en la autonomía de las personas con discapacidad - Layedra Chávez, Dennys Sebastián (2025)
The present research, entitled “Study of inclusive judicial practices from the social model and its impact on the autonomy of persons with disabilities”, aims to evaluate the degree of inclusion of the administration of justice in the Ecuadorian territory from the perspective of the social model focused on human rights. Its main interest was to analyze whether persons with disabilities can exercise their right to autonomy within the system. To achieve this, the study relied on a qualitative and transversal approach, using legal-analytical, sociological and dogmatic methods, combining different tools such as semi-structured interviews and surveys directed to judicial officials, persons with disabilities and human rights specialists, as well as detailed observation guides on physical and digital accessibility in judicial units of the country for data contrast. The results showed that, despite the existence of legal advances, there are still numerous barriers that hinder optimal inclusion, such as inadequate infrastructure, lack of reasonable accommodation, non-accessible information formats, and lack of updated protocols. In addition, it was observed that, in practice, many judicial operators continue to conceive disability from a medical-assistance approach, rather than understanding it as a human rights issue. This perspective creates a gap between national and international norms and their effective application, and, as a result, persons with disabilities continue to face obstacles that prevent them from exercising their rights freely and participating actively and independently in the administration of justice. Similarly, it was found that judicial officials were unaware of the content of the Convention on the Rights of Persons with Disabilities and of internal manuals of the Judicial Function. The lack of such knowledge limits the effectiveness of accessibility measures and, in many cases, perpetuates practices that end up excluding persons with disabilities. When comparing the country's situation with other Ibero-American cases, it was found that Ecuador lacked crucial tools such as barrier monitoring systems, ongoing training for officials, and budget planning adapted to these needs.